New Insights into the Role of Metformin Effects on Serum Omentin-1 Levels in Acute Myocardial Infarction: Cross-Sectional Study - Hayder M. Alkuraishy (Emergency Medicine International, 2015)
Background. Serum omentin-1 level was low in the most types of ischemic heart disease compared to normal subjects; it also dependently correlated with coronary heart disease; thus, omentin-1 is regarded as a novel biomarker in IHD. Objective. The aim of the present study was to establish the links between omentin-1 and acute myocardial infarction in metformin patients. Subjects and Methods. A cross-sectional study was performed on eighty-five patients with type II DM and acute MI. They are divided as follows: Group I, 62 patients with type II DM who received metformin prior to onset of acute MI; Group II, 23 patients with type II DM who did not receive metformin prior to onset of acute MI; and Group III, 30 normal healthy controls. Venous blood was drawn from each participant for determination of lipid profile, plasma omentin-1, cardiac troponin-I (cTn-I) and other routine tests. Results. Patients that presented with acute MI that received metformin show a significant difference in all biochemical parameters (p<0.001); metformin increases serum omentin-1 level and decreases serum cardiac troponin-I level compared with control subjects and nonmetformin treated patients. Conclusion. Metformin pharmacotherapy increases omentin-1 serum levels and may be regarded as a potential agent in the prevention of the occurrences of acute MI in diabetic patients.